Novos insetos sugadores (Hemiptera) atacando Eucalyptus cloeziana (Myrtaceae) em Minas Gerais, Brasil - de Menezes, Claubert Wagner Guimarães; Soares, Marcus Alvarenga; de Assis Júnior, Sebastião Lourenço; Fonseca, Arley José; Pires, Evaldo Martins; dos Santos, José Barbosa (EntomoBrasilis, 2012)
A migração de pragas de plantas nativas para a eucaliptocultura pode causar perdas significativas em sua produção. Foi relatada a ocorrência das cigarrinhas Aethalion reticulatum Linnaeus (Hemiptera: Aethalionidae) e Membracis lunata Fabricius (Hemiptera: Membracidae) em Eucalyptus cloeziana F. Muell. (Myrtaceae) no município de Couto de Magalhães de Minas, em Minas Gerais, Brasil. As espécies foram observadas em plantas de eucalipto em fase vegetativa no campo. A ocorrência desses insetos atacando o eucalipto indica sua migração de plantas frutíferas para o novo hospedeiro, não sendo recomendável a instalação de florestas de eucalipto próximas a áreas com fruticultura. New sucking insects (Hemiptera) attacking Eucalyptus cloeziana (Myrtaceae) in Minas Gerais, Brazil Abstract. The migration of pests of plants native to eucalyptus can cause significant losses in production. Been reported to occur of the leafhopper Aethalion reticulatum Linnaeus (Hemiptera: Aethalionidae) and Membracis lunata Fabricius (Hemiptera: Membracidae) in Eucalyptus cloeziana F. Muell. (Myrtaceae) in the municipality of Couto de Magalhães de Minas, Minas Gerais, Brazil. The species were observed in eucalyptus plants in the vegetative stage in the field. The occurrence of these insects attacking eucalyptus indicates their migration from fruit trees to the new host and is not recommended to install eucalyptus forests near areas with fruit trees.